(untitled) (Journal of Interdisciplinary Insights, 2025)
Teachers’ TPACK (Technological Pedagogical Content Knowledge) competence is a fundamental capability that every teacher must possess in the stage of educational informatization and intelligent development. It is an indispensable knowledge for teachers to conduct effective teaching. This paper elaborates on the connotation and structure of TPACK competence of primary and secondary school teachers, analyzes the necessity of enhancing their TPACK competence and the factors influencing primary and secondary school teachers’ TPACK competence in the context of artificial intelligence. Based on this, it explores the optimized pathways for enhancing primary and secondary school teachers’ TPACK competence empowered by artificial intelligence from multiple perspectives.